Photoreceptors and eyes of pikeperch Sander lucioperca, pike Esox lucius, perch Perca fluviatilis and roach Rutilus rutilus from a clear and a brown lake - Jokela-Määttä, Mirka; Viljanen, Martta; Nevala, Noora; Donner, Kristian; Brönmark, Christer (Journal of Fish Biology, 2019)
The photoreceptors and eyes of four fish species commonly cohabiting Fennoscandian lakes with different light transmission properties were compared: pikeperch Sander lucioperca, pike Esox lucius, perch Perca fluviatilis and roach Rutilus rutilus. Each species was represented by individuals from a clear (greenish) and a humic (dark brown) lake in southern Finland: Lake Vesijärvi (LV; peak transmission around 570 nm) and Lake Tuusulanjärvi (LT; peak transmission around 630 nm). In the autumn, all species had almost purely A2-based visual pigments. Rod absorption spectra peaked at c.526 nm (S. lucioperca), c. 533 nm (E. lucius) and c. 540 nm (P. fluviatilis and R. rutilus), with no differences between the lakes. Esox lucius rods had remarkably long outer segments, 1.5–2.8-fold longer than those of the other species. All species possessed middle-wavelength-sensitive (MWS) and long-wavelength-sensitive (LWS) cone pigments in single, twin or double cones. Rutilus rutilus also had two types of short-wavelength sensitive (SWS) cones: UV-sensitive [SWS1] and blue-sensitive (SWS2) cones, although in the samples from LT no UV cones were found. No other within-species differences in photoreceptor cell complements, absorption spectra or morphologies were found between the lakes. However, E. lucius eyes had a significantly lower focal ratio in LT compared with LV, enhancing sensitivity at the expense of acuity in the dark-brown lake. Comparing species, S. lucioperca was estimated to have the highest visual sensitivity, at least two times higher than similar-sized E. lucius, thanks to the large relative size of the eye (pupil) and the presence of a reflecting tapetum behind the retina. High absolute sensitivity will give a competitive edge also in terms of short reaction times and long visual range.